2006
DOI: 10.1128/aac.00163-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Posaconazole, Fluconazole, Itraconazole, Voriconazole, and Amphotericin B against a Large Collection of Clinically Important Molds and Yeasts

Abstract: The in vitro activity of the novel triazole antifungal agent posaconazole (Noxafil; SCH 56592) was assessed in 45 laboratories against approximately 19,000 clinically important strains of yeasts and molds. The activity of posaconazole was compared with those of itraconazole, fluconazole, voriconazole, and amphotericin B against subsets of the isolates. Strains were tested utilizing Clinical and Laboratory Standards Institute broth microdilution methods using RPMI 1640 medium (except for amphotericin B, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
303
4
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(359 citation statements)
references
References 37 publications
28
303
4
18
Order By: Relevance
“…Livio Pagano, 1 Oliver A. Cornely, 2,3 Alessandro Busca, 4 Morena Caira, 1 Simone Cesaro, 5 Cristiana Gasbarrino, 6 Corrado Girmenia, 7 Werner J. Heinz, 8 Raoul Herbrecht, 9 Cornelia Lass-Flörl, 10 Annamaria Nosari, 11 Leonardo Potenza, 12 Zdenek Racil, 13 1-2011-2012).…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Livio Pagano, 1 Oliver A. Cornely, 2,3 Alessandro Busca, 4 Morena Caira, 1 Simone Cesaro, 5 Cristiana Gasbarrino, 6 Corrado Girmenia, 7 Werner J. Heinz, 8 Raoul Herbrecht, 9 Cornelia Lass-Flörl, 10 Annamaria Nosari, 11 Leonardo Potenza, 12 Zdenek Racil, 13 1-2011-2012).…”
Section: Letters To the Editormentioning
confidence: 99%
“…[1][2][3] Among the available antifungals, amphotericin B (AmB) formulations and posaconazole demonstrate the most promising in vitro activities against Mucorales, 4,5 and their combination displays synergistic in vitro activity. 6,7 However, pre-clinical studies in neutropenic and diabetic ketoacidotic mice with IM reported no improvement in survival under a combination of posaconazole and liposomal amphotericin B (LAmB), compared to L-AmB monotherapy.…”
mentioning
confidence: 99%
“…12,16 However, in contrast to previous azole antifungals such as fluconazole and voriconazole, it also demonstrates enhanced in vitro activity against mucorales. 10 However, there are concerns about achieving reliable therapeutic levels in vivo to treat mucormycosis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Another study by Sabatelli et al compared the activity of posaconazole with itraconazole, fluconazole, voriconazole, and amphotericin B against 19,000 strains of yeasts and molds. 9 Posaconazole was more active than, or within 1 dilution of, the comparator drugs against 7000 isolates of Candida and Cryptococcus species. Also, posaconazole was active against species of Candida and Aspergillus which showed resistance to fluconazole, voriconazole, and amphotericin B, and was much more active than other triazoles against Zygomycetes.…”
Section: Efficacy Studies In Opcmentioning
confidence: 99%
“…11 Posaconazole has good activity against Candida species that are less susceptible to fluconazole (eg, C. krusei, C. guilliermondii, and C. dublinensis), but is less active against C. glabrata. 9 Based on MIC 90 values, posaconazole was found to be more potent than fluconazole and equal or more potent than itraconazole, voriconazole, and amphotericin B against these isolates.…”
Section: Resistance Issues: Azole-resistant Candida Speciesmentioning
confidence: 99%